The Effect of microRNA on the Production of Recombinant Protein in CHO Cells and its Mechanism - Liu, Hui-Ning; Dong, Wei-Hua; Lin, Yan; Zhang, Zhao-Hui; Wang, Tian-Yun (Frontiers in Bioengineering and Biotechnology, 2022)
Recombinant protein production by mammalian cells is the initial step in the manufacture of many therapeutic proteins. Chinese hamster ovary (CHO) cells are the most common host system to produce recombinant therapeutic proteins (RTPs). However, it is still challenging to maintain high productivity ensuring the good quality of RTPs produced by CHO cells. MicroRNAs(miRNAs) are short regulatory non-coding RNAs that can regulate cellular behavior and complex phenotypes. It has been found that miRNAs can enhance the expression level of recombinant proteins in CHO cells by promoting proliferation, resisting apoptosis, and regulating metabolism. miRNAs also can affect the quality of RTPs. In this review, we will discuss the effect and mechanism of miRNA on the expression level and quality of recombinant proteins in CHO cells.